PENGARUH DESKRIPSI PEKERJAAN DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI - -, Sarsono -; Suseno, Y.Djoko - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT This study aims to (1) analyze the significance of the effect of job descriptions, career development and job satisfaction on the performance of the employee, (2) analyze the moderating effect of job satisfaction in the job description of the employee's work performance, (3) analyze the moderating effect of job satisfaction in career development the performance of the employees. This study is the population using all respondents Technical Unit employees as the Education Office Grobogan regent a total of 97 people. Data collection techniques using observation, interviews, documentation, and questionnaires through validity and reliability. Regression test requirements using classical assumption test. Data analysis techniques using multiple regression analysis and regression testing moderating the absolute value of the difference and hypothesis testing through t test. The results of this study indicate that (1) job descriptions, career development and job satisfaction significantly influence job performance, (2) moderate the effect of job satisfaction on the performance of the job description of employees, (3) did not moderate the effect of job satisfaction on job performance of career development employee of the UPTD regent of Grobogan. Keywords: job descriptions, career development, job satisfaction, employee performance